INTRANASAL DELIVERY IN MANAGING ANTIBIOTIC RESISTANCE IN ‘BRAIN INFECTIONS’ - SHEHU, IBRAHIM AMINU; SHEHU, USMAN MUSA; DATTA, APARNA (International Journal of Current Pharmaceutical Research, 2022)
According to World Health Organization, WHO, antibiotic resistance is one of the biggest threats to global health, food security and development today. The means of delivering antibiotics to treat several brain infections, especially meningitis and encephalitis, have been inherently difficult, due to the presence of highly protective physiological barriers, mainly the blood-brain barrier (BBB), cerebrospinal fluid (CSF) that impairs the efficacy and bioavailability of antibiotics from reaching the susceptive organism. Many attempts have been made to optimize the therapeutic prognosis of such infections through the parenteral and intrathecal route of administration. These alternative routes have incited inadequate efficacy along with associated adverse effects. However, scientists have now considered the intranasal route (non-invasive) as a breakthrough to such inherent challenges. Moreover, several in vivo and ex vivo studies suggested evidence of the effectiveness of nose-to-brain delivery in treating bacterial and viral infections, thereby limiting the chance of antibiotic resistance. Targeting the multidrug resistance gram-positive and negative bacterias, a study was reported using nanoemulsion of Syzygiumaromaticum and Thymus vulgaris essential oils via the intranasal route. The result indicated the maximum inhibition of multi-drug resistance bacterias upon intranasal administration. Therefore, this study focuses to highlight the potential of intranasal delivery in the optimization of CNS infections and the prevention of antibiotic resistance.